The Effect of Cooperative Integrated Reading and Composition (CIRC) on Students’ Reading Comprehension Achievement - Sondang Manik; Milisi Sembiring; Lina Sriulina Br. Tarigan (Cetta: Jurnal Ilmu Pendidikan, 2021)
This study was intended to find out the effect of using Cooperative Integrated Reading and Composition on students reading comprehension. The population of this study was the students of Music Department English Department, Medan with three parallel classes, and there are (120) students totally. The sample of the research was two classes, which were selected by using cluster random sampling technique, the total were (80) students. The sample was divided into two groups; the first group is 40 students, (Grade X 1) which was the experimental group. The second group is 40 students, (Grade X 2) which was the control group. The experimental group was taught by using Cooperative Integrated Reading and Composition while control group was taught without using questioning strategy. The instrument used for collecting the data was test in the form of multiple choices with the total number of 20 questions. The tests were divided into two; pre-test and post-test. The reliability of the test was 0.9. After the data had been collected, they were analyzed by using t-test formula in order to see whether the discussion method significantly affects students reading comprehension. The result of the analysis showed that the t-observed (4.8), it was higher than the t-table (2.024) with the level of significant (0, 05) and the degree of freedom (df) (38). The result of the analysis showed that the hypothesis of the study was accepted. It was concluded that questioning strategy significantly affects students reading comprehension.